Editorial: gut microbiota profile in patients with autoimmune hepatitis—a clue for adjunctive probiotic therapy? Authors' reply. Issue 2 (26th June 2020) - Liwinski, Timur; Schramm, Christoph
Abstract : LINKED CONTENT This article is linked to Liwinski et al and Granito et al papers. To view these articles, visit https://doi.org/10.1111/apt.15754 and https://doi.org/10.1111/apt.15795 .